Self-efficacy and Quality of Working Life: the mediating role of Self-esteem - Coelho, Rita; Costa, Vítor; Esgalhado, Graça (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2024)
Work-related quality of life (WRQoL) is an important variable to study nowadays, given its impact on workers’ behavior and well-being. Seeking to understand its antecedents, this paper presents empirical research with the aim of analyzing the relationships between occupational self-efficacy, self-esteem and WRQoL. Based on the literature review, a theoretical model is presented, considering self-esteem as a mediating variable between occupational self-efficacy and WRQoL. Participants were 607 workers, with an average age of 37.0 years. The results showed that occupational self-efficacy and self-esteem have a significant positive relationship with WRQoL. It was also found that self-efficacy has an indirect effect on WRQoL, mediated by self-esteem. Conclusions point out to the importance of the development of personal resources, to promote positive personal and organizational outcomes, such as job satisfaction and general well-being, with implications for psychological practice and health promotion in an occupational context.